MUTAGENICITY OF KOJIC ACID PRODUCED FROM WILD TYPE Aspergillus oryzae - Tariq Ibrahim; Salah Ahmed; Younis Younis; Michael Chikindas (Mesopotamia Journal of Agriculture)
Kojic acid (KA) is a multipurpose natural compound, commonly used in the food and cosmetics industry. It is produced by different types of molds especially by the species Aspergillus oryzae. In this study, we test the mutagenicity of local produced kojic acid PKA produced by the wild-type strain of A. oryzae as well as the standard commercially produced kojic acid SKA and ascorbic acid SAA for comparison to stop food manufacturers doubts about using KA. AMES test with Salmonella enterica ATCC 29629 strain TA1535 and S9 liver enzyme for metabolic activation of the tested compounds were utilized in this study by direct and indirect methods were used in the test. The study results showed that the tested PKA kojic acid had cannot induce reverse mutation in the strain ATCC 29629TA1535 used in the test in contrast with the positive control in direct and indirect methods, even where the tested acids were treated with S9 liver enzymes with or without pre-incubation for three hours at 37 °C hadn’t given positive results on TA1535. The used concentration of 1% and 10% S9 liver enzymes hadn’t metabolically activated the three acids. 6 mg/plate of KA inhibited the growth of TA1535. SAA gave the same negative results as PKA and SKA. In conclusion, the tested PKA produced by wild-type A. oryzae was not has mutagenic effect on bacterial strain TA1535   and gave the same effect as the commonly used as food additive SAA and SKA even when treated with S9 liver enzymes.